2020
DOI: 10.3928/01477447-20200827-06
|View full text |Cite
|
Sign up to set email alerts
|

Locking Plate Combined With Endosteal Fibular Allograft Augmentation for Medial Column Comminuted Proximal Humeral Fracture

Abstract: The goal of this study was to evaluate the role of endosteal fibular allografts in the treatment of medial column comminuted proximal humerus fractures with a locking plate. The authors retrospectively analyzed the clinical outcomes of 63 patients (21 men and 42 women) who had proximal humerus fractures with a comminuted medial column and were treated at Shanghai Jiao Tong University Affiliated Sixth People's Hospital, Shanghai, China, with a locking plate, either alone or in combination with a fibular strut a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…Contrary to the prior hypothesis, our findings suggest that the likelihood of a clinically relevant benefit is small at 12 months, because the 95% CI typically excluded the MCID (10 points for the DASH score). This is supported by 3 previous studies [24][25][26] , but is inconsistent with others as well as a meta-analysis 7,10,13,27 . The discrepancies could be partially explained by heterogeneity in the study populations; most of the studies were designed to include elderly patients with displaced fractures and only 1 study focused on medial column comminuted fractures 7 , even though fractures with medial column comminution should be the typical cases in which additional medial supports are likely to be required.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Contrary to the prior hypothesis, our findings suggest that the likelihood of a clinically relevant benefit is small at 12 months, because the 95% CI typically excluded the MCID (10 points for the DASH score). This is supported by 3 previous studies [24][25][26] , but is inconsistent with others as well as a meta-analysis 7,10,13,27 . The discrepancies could be partially explained by heterogeneity in the study populations; most of the studies were designed to include elderly patients with displaced fractures and only 1 study focused on medial column comminuted fractures 7 , even though fractures with medial column comminution should be the typical cases in which additional medial supports are likely to be required.…”
Section: Discussioncontrasting
confidence: 47%
“…This is supported by 3 previous studies [24][25][26] , but is inconsistent with others as well as a meta-analysis 7,10,13,27 . The discrepancies could be partially explained by heterogeneity in the study populations; most of the studies were designed to include elderly patients with displaced fractures and only 1 study focused on medial column comminuted fractures 7 , even though fractures with medial column comminution should be the typical cases in which additional medial supports are likely to be required. Furthermore, no randomized allocation or appropriate casecontrol matching was conducted, meaning that the intergroup comparability was questionable in previous studies.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…The measurement scales used in each trial varied, and most studies used more than one scale to assess the postoperative function, including the Constant score/Constant–Murley score (CMS) [ 22 ], American Shoulder and Elbow Surgeons (ASES) score [ 23 ], disability of arm–shoulder–hand (DASH) score [ 24 ], and Simple Shoulder Test (SST) [ 25 ]. After excluding two studies without sufficient data for the analysis [ 9 , 20 ], data syntheses were conducted based on six studies [ 10 , 16 19 , 21 ] and showed statistically significant differences in functional recovery in favour of the application of FSA (CMS: MD 5.07; 95% CI 3.40–6.74; I 2 = 0.00%; 95% PI 2.361–7.78; ASES: MD 5.08; 95% CI 3.67–6.49; I 2 = 0.00%; 95% PI 1.98–8.18), without obvious evidence of heterogeneity (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%